Soil salinity and moisture measurement system for grapes field by wireless sensor network. Issue 1 (31st December 2016) - Bhanarkar, M.K.; Korake, P.M.
Abstract: Soil moisture and salinity measurement are the essential factors for crop irrigation as well as to increase the yield. Grapes eminence depends on the water volume contents in soil and soil nutrients. Based on these conditions, we determined water demand for best quality of grapes by wireless sensor network (WSN). Using lot of chemical fertilizers increases soil salinity but reduces soil fertility, soil salinity defines electrical conductivity or salty soil. Precise agriculture systems are integrated with multiple sensors to monitor and control the incident. Integrated WSN is designed and developed to measure soil moisture and salinity. ATmega328 microcontroller, XBee and Soil sensors are integrated across the system. This system is more competent, it can be helpful to automatic irrigation system and soil salinity monitoring.